New diagnostic methods for detecting dental caries - Integrative review (Research, Society and Development, 2020)
The development of new methods in the detection of caries aims to facilitate the diagnosis of incipient caries lesions, overcoming the deficiency of conventional methods. Objective: To show the new techniques to help in the detection of incipient injuries. Method: This is an integrative review of new diagnostic methods for detecting dental caries carried out between May and June 2020, based on the acquisition of scientific data from SciELO, LILACS, Pubmed platforms. This review refers to the period from 2010 to 2020 in the languages: Portuguese, English. The following descriptors were used to perform the individual search: Dentistry; Caries; Diagnosis, in addition to the crossing between them using the Boolean operator “AND”. Result: after conducting a literature search, ten articles were found related to new diagnostic methods for detecting dental caries. Conclusion: Despite the emergence of promising new methods, visual inspection remains the method of choice. The other methods should be used as auxiliary tools to obtain a more accurate diagnosis.